Wapwapek Ambover Traditional Wisdom of the Napa People in Dispute Resolution - yustus pondayar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This research aims to understand Wapwapek Ambover: the traditional wisdom of the Napa People (Subetnik Biak) used in dispute resolution which can be adopted as a contextual model that is considered suitable for resolving disputes effectively, thoroughly and with dignity. The method used in this exploratory research is supported by two empirical research methods, namely exploratory and descriptive methods to obtain ethnoscientific data on the Napa People, which is still relevant in dispute resolution supported by triangulated interview and observation techniques. The results of the research found that Wapwapek Ambover is the wisdom of the Napa people in dispute resolution efforts, namely the traditional court called fuknuser under the Kankain Kakarara Vyak institution, and four forms of violence: structural (political), resolved with material fines, which ends with the sacred ritual of Wapwapek Ambover " reed-cutting oath', as a model for achieving harmony and peace. Wapwapek Ambover is a model of effective dispute resolution, according to Napa people.